menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve the system. Give answer as ( x , y , z ) 2 x − 2 y + 4 z = 0 − 6 x − 4 y − 4 z = 2 − 3 x − 8 y + 4 z = 1 ( x , y , z ) = ( , , )
asked
Feb 25, 2022
30.2k
views
4
votes
Solve the system. Give answer as
(
x
,
y
,
z
)
2
x
−
2
y
+
4
z
=
0
−
6
x
−
4
y
−
4
z
=
2
−
3
x
−
8
y
+
4
z
=
1
(
x
,
y
,
z
)
=
(
,
,
)
Mathematics
college
Youhans
asked
by
Youhans
5.2k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
Answer:
howwwwww
Explanation:
it's alot going on
Ian Yang
answered
Mar 4, 2022
by
Ian Yang
4.9k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org